1985
DOI: 10.1017/s002193200001600x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and age at secondary sterility in rural Bangladesh

Abstract: In a prospective study of 2324 women in Matlab, Bangladesh, the occurrence of primary and secondary sterility by age groups was examined. The results were related to the nutritional status of the women, as assessed by measurements of height, weight, arm circumference and ponderal index. There is evidence that nutritional status is an important factor in estimated age at sterility, with thinner women experiencing a slightly earlier menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Within each study group, median ages at menopause were later than mean recalled ages at menopause as expected due to methodological differences (Sievert and Hautaniemi 2003). Average ages at menopause are earlier among these upper middle class women in Sylhet compared to women recruited from Matlab, Bangladesh (Karim et al 1985).…”
Section: Predictionmentioning
confidence: 82%
See 4 more Smart Citations
“…Within each study group, median ages at menopause were later than mean recalled ages at menopause as expected due to methodological differences (Sievert and Hautaniemi 2003). Average ages at menopause are earlier among these upper middle class women in Sylhet compared to women recruited from Matlab, Bangladesh (Karim et al 1985).…”
Section: Predictionmentioning
confidence: 82%
“…In contrast, there are few studies available for age at menopause from women in Bangladesh, the country of focus here. In an earlier study, Karim et al (1985) reported one of the lowest median ages at menopause in the literature at 43.6 years in Bangladesh. These data, however, come from Matlab Thana, a poor socioeconomic area near the capital city of Dhaka, in stark contrast to the affluent middle class women from Sylhet in northeast Bangladesh who are the focus of study in this paper.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations